Mechanics of nickel–titanium shape memory alloys undergoing partially constrained recovery for self-healing materials. (September 2018) - Salowitz, Nathan; Correa, Ameralys; Santebennur, Trishika; Dorri Moghadam, Afsaneh; Yan, Xiaojun; Rohatgi, Pradeep
Engineered self-healing materials seek to create an innate ability for materials to restore mechanical strength after incurring damage, much like biological organisms. This technology will enable the design of structures that can withstand their everyday use without damage but also recover from damage due to an overload incident. One of the primary mechanisms for self-healing is the incorporation of shape memory fibers in a composite type structure. Upon activation, these shape memory fibers can restore geometric changes caused by damage and close fractures. To date, shape memory–based self-healing, without bonding agents, has been limited to geometric restoration without creating a capability to withstand externally applied tensile loads due to the way the shape memory material has been integrated into the composite. Some form of bonding has been necessary for self-healing materials to resist an externally applied load after healing. This article presents results of new study into using a form of constrained recovery of nickel–titanium shape memory alloys in self-healing materials to create residual compressive loads across fractures in the low temperature martensitic state. Analysis is presented relating internal loads in self-healing materials, potentially generated by shape memory alloys, to the capability to resist externally applied loads. Supporting properties were experimentally characterized in nickel–titanium shape memory alloy wires. Finally, self-healing samples were synthesized and tested demonstrating the ability to resist externally applies loads without bonding. This study provides a new useful characterization of nickel–titanium applicable to self-healing structures and opens the door to new forms of healing like incorporation of pressure-based bonding.